The Influence of Electronic Word of Mouth (EWOM) on Repurchase Intention Brand Image as a Mediating Variable: Study on Consumers of Maybelline Blush Product in Bandung - Sahrin Nuru Hayyu; Abdul Ahmad Hafidh Nurmansyah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of this study is to examine the influence of electronic word of mouth (eWOM) on repurchase intention, mediated by brand image, among consumers of Maybelline blush products. The instruments used in this research have passed validity and reliability tests. These instruments were utilized to collect data from respondents who have purchased Maybelline blush and are aged between 15-45 years old and have experience using Maybelline blush. A total of 138 individuals participated in this study. The data collection technique employed was cross-sectional or one-shot study. The data analysis technique used was multiple linear regression conducted using SPSS version 25, supplemented by the Sobel test. Out of ten proposed research hypotheses, seven were supported by empirical data. The findings of this study indicate that brand image mediates the influence of valence of opinion and content, as dimensions of electronic word of mouth (eWOM), on repurchase intention. Meanwhile, the use of other concepts to directly influence repurchase intention could be suggested for future research. These research results are beneficial for stakeholders involved in designing strategies relevant to enhancing these attribute qualities.